Pengaruh Lingkungan Keluarga terhadap Minat Belajar Siswa (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
This research aims to determine the effect of the family environment on students’ learning motivation. The scope of the research is by reading relevant journal articles. The research method used in this research is descriptive qualitative, where the data sources are obtained from relevant journal articles. The results of this study indicate that the research that has been carried out is proven to be true regarding the family environment having an influence on students’ learning motivation. Attention from parents is very influential in motivating children to learn. the family environment is the most important environment for children, the family environment especially the parents of a student must have a very important role in motivating children to learn, so that a child learns and can get excellent learning outcomes at school. High learning motivation affects student learning outcomes. Students are committed to the exercises presented by the teacher, and students appreciate to explore the material so that they can answer the questions presented by the teacher as well as possible. On the other hand, students who do not have the desire to learn in themselves will have learning difficulties and will not do well in school.